Da energia que se planta à sujeição camponesa: o Programa Nacional de Produção e Uso de Biodiesel e seus rebatimentos no alto sertão sergipano - Rodrigues, Jamile Oliveira (2013)
The project entitled From the energy which is planted to the peasants subjects: The National Program for Production and Use of Biodiesel and its effect in the backwoods of Sergipe , analyzes the contradictions of the National Program for Production and Use of Biodiesel in the backwoods of Sergipe and its effect in the peasants production. The study got back the debate about the discovery of oil as a great energy potential during the Second Industrial Revolution, and later, the increase of consumption through the economic activities, which brought up a shortage context of this resource, responsible for imposing a review of the world energetic base. The demand for a new energetic base is joined with the creation of a new development approach that suggests the rational and sustainable use of natural resources. In this outlook, the continuation of the production model depends on the creation of this new base, and Brazil, created many programs to support the energy production, especially, through agrofuels, whose history brought changes in the Brazilian rural areas. In Sergipe, the National Program for Production and Use of Biodiesel has been introduced in the country since 2007, presenting as an objective, the diesel production through the sunflower cultivation, and making it stand out by the promises of bringing environmental, social and economic benefits. Actually, the National Program for Production and Use of Biodiesel expresses the importance of the context that no structure change is highlighted to definitely stamp out the poverty in the country. In the study area, a program was observed that after spatializing, it went deeper into the vulnerability of the country person to the market guidelines, as the oil seeds production happens under the command of an outside agent, supporting the capitalist relations nowadays.